Monitoring the Socio-Economic Conditions in Uruguay - Hernán Winkler (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This document is the first of a series of reports on the socio-economic situation in Uruguay. It is mainly based on a wide range of distributional, labor and social statistics computed from microdata collected by the Encuesta Continua de Hogares (ECH) from 1989 to 2003. Data has also been drawn from other sources and the existing literature. In contrast to the significant advances in poverty reduction recorded since the mid-eighties, in the last years Uruguay witnessed a deterioration of distributional, labor and social conditions. However, the country's social performance is still one of the best in the region.
Keywords: D3; I32; O54; 330; poverty; inequality; education; labor; wages; employment; Uruguay